Yurt dışından dönen Türk öğrencilerin uyum düzeyleri ve benlik algıları - F. Gül AKBALIK; B. Dilek KARADUMAN; E. Arzu ORAL; Belka ÖZDOĞAN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This study examines the adaptation and self perception level differences between the Turkish students who had been and not been in a foreign country. A total of 299 students, attending three different Anatolian high schools, participated in the study. Three groups of students were compared; the first group had come from abroad within a year, the second group had come more than a year ago and the third group had not been in a foreign country. The results demonstrated that there were no differences between the group's Total, Social Adjustment Subscale and Academic Adjustment Subscale scores. The exception for this were the fırst group, who scored lower on School Adaptation Subscale of the Adjustment Scale than those of the other two groups. Additionally, It was found that the third group scored higher on only one of the six sub-scales of the Piers-Harris' Self Concept Scale, namely the Cognitive and Academic Performance Subscale from the other two groups